2018
DOI: 10.1037/pas0000628
|View full text |Cite
|
Sign up to set email alerts
|

College student mental health: An evaluation of the DSM–5 self-rated Level 1 cross-cutting symptom measure.

Abstract: The Self-Rated Level 1 Cross-Cutting Symptom Measure was developed to aid in clinical decision-making for clients seeking psychiatric services and to facilitate empirical investigation of the dimensional nature of mental health issues. Preliminary evidence supports its utility with clinical samples. However, the brief, yet comprehensive structure of the Level 1 measure may benefit a high-risk population that is less likely to seek treatment. College students have high rates of hazardous substance use and co-oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(84 citation statements)
references
References 22 publications
2
80
2
Order By: Relevance
“…Participants were college students ( n = 7,307) recruited to participate in an online survey in exchange for research participation credit from Psychology Department Participant Pools at 10 universities across 10 U.S. states (for more information of study procedures and sample, see Bravo et al., ). To minimize burden on participants, we utilized a planned missing data design, also known as matrix sampling (Graham et al., ; Schafer, ).…”
Section: Methodsmentioning
confidence: 99%
“…Participants were college students ( n = 7,307) recruited to participate in an online survey in exchange for research participation credit from Psychology Department Participant Pools at 10 universities across 10 U.S. states (for more information of study procedures and sample, see Bravo et al., ). To minimize burden on participants, we utilized a planned missing data design, also known as matrix sampling (Graham et al., ; Schafer, ).…”
Section: Methodsmentioning
confidence: 99%
“…reports of physical fights) [19]. Although several studies have used the MACQ (or B-MACQ) to assess marijuana-related negative consequences [20][21][22][23][24][25][26], no published study to date has examined the MACQ outside North America (i.e. United States and Canada).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have confirmed the use of the L1-CCSM measure for identification of different psychiatric presentations. [34][35][36] In a study with university students, the measure had a good internal validity and concurrent validity. 34 Test-retest reliability of the measure was good in a study with adults.…”
Section: Sample Sizementioning
confidence: 99%
“…[34][35][36] In a study with university students, the measure had a good internal validity and concurrent validity. 34 Test-retest reliability of the measure was good in a study with adults. 35 Level 2: disorder-specific assessment.…”
Section: Sample Sizementioning
confidence: 99%